Health, work ability and work motivation: determinants of labour market exit among German employees born in 1959 and 1965 - Anita Tisch (Journal for Labour Market Research, 2015)
In Germany, 20?% of annual retirees withdraw from the labour market early due to work disability. Meanwhile, it has been argued that in modern societies, not only health but also work motivation and self-perceived work ability have growing influences on individual immediate employment decisions. Moreover, work motivation and work ability have been argued to mediate the relationship between health and labour market exit. Therefore, this article analyses the mediational effect of work ability and work motivation in the relationship between health and labour market exit. The study employs data from the lidA Cohort Study (German Cohort Study on Work, Age, Health, and Work Participation) (n?=?3796), which is linked to register data from the Federal Employment Agency. The data linkage facilitates following the survey participants' work trajectories even after their interviews and allows for a one-year follow-up study. The sample of the lidA study comprises two cohorts of the ageing German baby boom generation (employees born in 1959 and 1965). The baby boomers are chosen because they are the first cohorts whose official retirement age has been raised to 67 years of age and for whom almost no possibilities of early retirement are available aside from disability pensions. This article reveals an increased probability of labour market withdrawal within one year after individuals report health impairments, low physical or mental work ability, or a preference for exiting employment (low work motivation). The findings further show that low work motivation and low self-perceived work ability can only partly mediate the relationship between impaired health and labour market withdrawal (<?10?%).
Keywords: I14; J6; Z13; 330; ältere Arbeitnehmer; Berufsausstieg - Determinanten; Arbeitsfähigkeit; Arbeitsmotivation; Gesundheitszustand; Selbsteinschätzung; IAB-Datensatz Leben in der Arbeit; Erwerbsunfähigkeitsrente